Mist nebulizer versus heated humidifier on endotracheal tube patency in spontaneously breathing intubated patients: A prospective, randomized controlled trial - Vijaya P Patil; Prakash Deb; Vandana Agarwal; Pavan Kumar (Wolters Kluwer Medknow Publications, 2023)
Background and Aims: Using a humidifier in intubated patients is now a standard of care as the humidifying effect of the upper airway is lost. We conducted this study to compare the efficacy of a heated humidifier (HH) with the more commonly used conventional mist nebulizer on overnight intubated and spontaneously breathing post-operative patients. Material and Methods: This prospective, randomized control trial included 60 post-operative overnight intubated and spontaneously breathing patients, of which 30 patients were allocated to the HH group and 30 to the mist nebulizer group. The reduction of endotracheal tube (ETT) patency was measured quantitatively by the difference between the pre-intubation and immediate post-extubation ETT volume and compared between the two groups. Also, the characteristics of secretion, the temperature of inspired gas at the Y-piece, and the frequency of refilling the humidifier chamber were recorded and compared. Results: The reduction of ETT volume was significantly more in the mist nebulizer group compared to the HH group (P-value 0.00026). The mean temperature of the inspired gas (°C) was higher in the HH group (P-value < 0.0001). More patients in the mist nebulizer group had thicker (P-value 0.057) and drier secretions (P-value 0.005) compared to the HH group. None of the patients in the HH group required refilling of the humidifier chamber while the mean frequency of the refilling was 3.5 times per patient in the mist nebulizer group. Conclusion: HH may be preferred over mist nebulizer as the latter requires more frequent refilling which may not be practically possible in a busy recovery room rendering the patient at the risk of inhaling dry gas and consequent thick and dry secretions with decreased ETT patency.